Underground mining method selection and preliminary techno-economic mine design for the Wombat orebody, Kylylahti deposit, Finland - Peskens, T.W. (author) (2013)
Mining method selection lies at the basis of every mining operation and is essential for maximizing economic return. Especially in the current market with decreasing metal prices selecting the right method can mean the difference between a viable and a non-viable operation. More importantly the right mining method increases the safety of employees and secures the production. The Kylylahti underground copper mine, owned by Altona Mining ltd. is located in Northern-Karelia, Finland. This deposit consists of two orebodies, the upper Wallaby and the lower Wombat. Longitudinal bench stoping is proposed for the Wallaby and Wombat orebodies. The Wallaby orebody is currently mined using the proposed method. However, different orebody characteristics suggest a more suitable mining method for the Wombat orebody. This work determines the mining method which maximizes economic return for the Wombat orebody. This is a three phase process. First phase is the mining method selection on technical suitability to the orebody; for which two methods are. The UBC method is applied first resulting in the selection of the area of sublevel stoping methods. Later a new technique is introduced to optimize the mining method selection process and to control the wide spectrum of mineral deposits. This technique is called the Fuzzy Analytic Hierarchy Process approach and is based on Multiple Criteria Decision Making. Six factors specifically applicable to the Kylylahti mine are used as input for the approach resulting in transverse bench stoping as the most suitable method for the Wombat orebody. In the subsequent phase, the rock mass properties of the ore zone and the host rock masses are calculated using the Q-classification method. These values are combined with the results of in situ stress measurements to determine the stability of the open stopes at different depths. Dimensions of the stopes are determined depending on the resulting stability limits on stope height, width and length. Applying these stope limits a preliminary mine ...